Investigation of residual stress induced crack closure and its effects on fatigue in metal matrix composites - Korsunsky, A; Withers, P (Trans Tech Publications, 1997)
The effects of fatigue crack closue induced by crack-tip plasticity, and by the long range residual stresses in particular, on crack growth rates were considered for an aluminium alloy matrix composite reinforced with particulate SiC. This included the analysis of experimental measurements of crack growth rates and closure levels in composite and unreinforced alloy speciments, mapping of internal strains in the matrix and the reinforcing particles using neutron diffraction measurements, and numerical modelling of crack opening under the combination of residual stresses and applied loads, performed using the distributed dislocation technique and the finite element method. Experimental evidence suggests very high levels of crack closure in water-drenched composite samples, which may be decreased by annealing (reduction of residual stresses). A model of discontinuous crack closure has been proposed, whereby the first contact of crack faces upon unloading of a speciment, occurs away from the crack front, in the vicinity of the notch root. This notion is supported by experimental evidence obtained from neutron diffraction measurements, which show crack tip stress intensification in fully unloaded samples. This results from the 'wedging' effect caused by crack face contact in the near-notch region. The predictions obtained using this model were compared with the experimental data, with particular emphasis on the effect on the specimen compliance curves at various levels of quench-induced macroscopic residual stresses, applied bending moments, R-ratios, fatigue crack lengths, etc.